Comment on Feige's Paper "Reflections on the Meaning and Measurement of Unobserved Economies: What do we really know about the 'Shadow Economy'?" - Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2016)
This comment provides a reply to Prof. Feige's paper with the title “Reflections on the Meaning and Measurement of Unobserved Economies: What do we really know about the `Shadow Economy'?”, in which Prof. Feige heavily criticizes me. I show that the same critique which Prof. Feige raises against me can be put forward to his results on the non-observed economy. Moreover, I show that my dataset is appropriately documented and I also address the problem of calibration and normalization issues when undertaking a MIMIC estimation. In the concluding chapter I suggest that a joint paper should be written in which all the pros and cons of each method of estimating the size and development of the non-observed/shadow economy are presented and criticized.
Keywords: C51; C82; E26; E41; H26; K42; O17; 330; shadow economy; non-observed economy or income; macro approaches; MIMIC and currency demand approach